Composite zinc-based negative electrode, preparation method and nickel-zinc battery

CN120809759BActive Publication Date: 2026-10-09SOUTH CHINA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510857690.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2026-10-09
Estimated Expiration
2045-06-25

AI Technical Summary

Technical Problem

[0004]为解决上述技术问题,本发明的目的在于提供一种复合锌基负极、制备方法及镍锌电池,通过功能化材料与基底极片的结合,有效解决了碱性镍锌电池负极存在的锌枝晶生长、腐蚀析氢及表面钝化导致电池循环寿命衰减的问题

Benefits of technology

[0020] This invention adds only one step to the existing nickel-zinc battery anode production process: a functionalized material dispersion coating process. This eliminates the need for significant modifications to the anode production process and avoids the conventional secondary conductive coating treatment of zinc oxide powder, simplifying the production flow. The functionalized material forming the coating layer on the substrate electrode of this invention, through the dual effects of chemical cross-linking and interfacial bonding, significantly reduces the swelling rate of the coating layer while improving the interfacial bonding strength between the coating layer and the substrate electrode. This invention, through the combination of functionalized materials and the substrate electrode, effectively solves the problems of zinc dendrite growth, corrosion hydrogen evolution, and surface passivation leading to battery cycle life degradation in alkaline nickel-zinc battery anodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120809759B_ABST
    Figure CN120809759B_ABST
Patent Text Reader

Abstract

The application discloses a kind of composite zinc-based negative electrode, preparation method and nickel-zinc battery, composite zinc-based negative electrode includes base electrode sheet and functional material, functional material is coated on base electrode sheet, and forms coating on base electrode sheet, wherein, functional material includes poly (3,4-ethylenedioxythiophene), dodecyl benzene sulfonic acid and 3-glycidyl ether oxypropyl trimethoxysilane, wherein, poly (3,4-ethylenedioxythiophene) and dodecyl benzene sulfonic acid form PEDOT:DBSA material, 3-glycidyl ether oxypropyl trimethoxysilane is added in PEDOT:DBSA material, and form functional material.The application is combined by functional material and base electrode sheet, effectively solve the problem that zinc dendrite growth, corrosion hydrogen evolution and surface passivation cause battery cycle life attenuation existing in alkaline nickel-zinc battery negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, specifically relating to a composite zinc-based anode, its preparation method, and a nickel-zinc battery. Background Technology

[0002] Aqueous nickel-zinc batteries are alkaline rechargeable batteries that use nickel hydroxide as the positive electrode active material, metallic zinc as the negative electrode active material, and potassium hydroxide solution as the electrolyte. They have a nominal voltage of 1.6V and typically operate at ≥1.6V. Nickel-zinc batteries have an energy density close to that of lithium-ion batteries. They use recyclable nickel and zinc metal, resulting in lower recycling costs than lead-acid / lithium batteries. Compared to nickel-cadmium batteries, nickel-zinc batteries eliminate cadmium pollution. Compared to lithium-ion batteries, they offer safety and cost advantages, with no risk of combustion or explosion. However, dendrite growth and hydrogen evolution side reactions occurring on the zinc negative electrode during cycling lead to decreased cycle stability, becoming a core issue restricting their commercial application.

[0003] Currently, industry improvements to nickel-zinc battery anodes mainly focus on two approaches: ZnO powder modification and electrode structure optimization. ZnO powder modification refers to improving the anode by coating or doping the surface of ZnO powder to enhance battery cycle life, but this approach requires complex precursor processing. Electrode structure optimization involves using a polyvinyl alcohol coating to isolate the anode from the electrolyte, suppressing hydrogen evolution and dendrite growth. However, due to the insulating properties of polyvinyl alcohol, a carbon layer is required on the electrode to maintain conductivity, further complicating the anode structure. Therefore, existing solutions to address hydrogen evolution and dendrite growth in nickel-zinc battery anodes still have shortcomings. Based on this, this invention proposes a conductive polymer-coated composite zinc-based anode, its preparation method, and a nickel-zinc battery. Summary of the Invention

[0004] To address the aforementioned technical problems, the present invention aims to provide a composite zinc-based anode, a preparation method, and a nickel-zinc battery. By combining functionalized materials with the substrate electrode, the invention effectively solves the problems of zinc dendrite growth, corrosion hydrogen evolution, and surface passivation leading to battery cycle life degradation in alkaline nickel-zinc battery anodes.

[0005] To achieve the above-mentioned objectives, the technical solution adopted by the present invention is as follows:

[0006] In a first aspect, the present invention provides a composite zinc-based negative electrode, comprising a substrate electrode and a functionalized material, wherein the functionalized material is coated on the substrate electrode to form a coating layer on the substrate electrode, wherein the functionalized material comprises poly(3,4-ethylenedioxythiophene), dodecylbenzenesulfonic acid and 3-glycidyl etheroxypropyltrimethoxysilane, wherein poly(3,4-ethylenedioxythiophene) and dodecylbenzenesulfonic acid form a PEDOT:DBSA material, and 3-glycidyl etheroxypropyltrimethoxysilane is added to the PEDOT:DBSA material to form the functionalized material.

[0007] Preferably, the thickness of the coating layer is 0.02–20 μm.

[0008] Preferably, the substrate electrode comprises zinc oxide, zinc metal, a conductive agent, and a binder, wherein the mass ratio of zinc oxide, zinc metal, conductive agent, and binder is (60-90):(5-30):(3-15):(2-10).

[0009] More preferably, the thickness of the substrate electrode is 180–200 μm.

[0010] In a second aspect, the present invention provides a method for preparing a composite zinc-based negative electrode, as follows:

[0011] Preparation of functionalized materials: Triton X-100 and 3,4-ethylenedioxythiophene (EDOT) were added to an aqueous solution of sodium dodecylbenzenesulfonate and stirred until a uniform emulsion was formed. Then, a salt solution containing persulfate and ferric salt was added dropwise to the emulsion. After reacting for 48 hours, the emulsion was broken and the mixture was centrifuged and dried to obtain PEDOT:DBSA powder. The PEDOT:DBSA powder was dispersed in an aqueous ethanol solution and 3-glycidyl etheroxypropyltrimethoxysilane was added to prepare a dispersion of the functionalized material.

[0012] Coating: A dispersion containing PEDOT:DBSA powder and GOPS crosslinking agent is drop-coated onto the substrate electrode, vacuum dried at 40°C, the solvent of the dispersion is dried off, and then transferred to 80°C for further drying and curing for 2 hours to form a composite zinc-based negative electrode with a coating layer.

[0013] Preferably, PEDOT:DBSA powder is dispersed in ultrapure water containing 20% ​​anhydrous ethanol to prepare a 1% dispersion, and GOPS is added, with GOPS accounting for 0.05-2 vol.% of the dispersion.

[0014] Preferably, the concentration of the sodium dodecylbenzenesulfonate aqueous solution is 0.125 mol / L, and the molar ratio of SDBS to EDOT is 1:2.

[0015] Preferably, in the salt solution, the persulfate includes Na2S2O8, the molar ratio of persulfate to EDOT is 1:1, and the ferric salt includes FeCl3·6H2O, wherein the ferric salt accounts for 1 wt.% of the mass of the persulfate in the salt solution.

[0016] Preferably, the preparation method further includes the preparation of a substrate electrode:

[0017] Zinc oxide, metallic zinc, conductive agent, and binder are mixed evenly, then coated onto the current collector and rolled into shape. The thickness of the substrate electrode is controlled during the rolling process. The electrode is then dried in a vacuum drying oven at 60–100°C to form a porous zinc-based negative electrode.

[0018] In a third aspect, the present invention also proposes an application of a composite zinc-based anode, wherein the above-mentioned composite zinc-based anode is used in an alkaline nickel-zinc battery.

[0019] Beneficial effects:

[0020] This invention adds only one step to the existing nickel-zinc battery anode production process: a functionalized material dispersion coating process. This eliminates the need for significant modifications to the anode production process and avoids the conventional secondary conductive coating treatment of zinc oxide powder, simplifying the production flow. The functionalized material forming the coating layer on the substrate electrode of this invention, through the dual effects of chemical cross-linking and interfacial bonding, significantly reduces the swelling rate of the coating layer while improving the interfacial bonding strength between the coating layer and the substrate electrode. This invention, through the combination of functionalized materials and the substrate electrode, effectively solves the problems of zinc dendrite growth, corrosion hydrogen evolution, and surface passivation leading to battery cycle life degradation in alkaline nickel-zinc battery anodes. Attached Figure Description

[0021] Figure 1 The diagram shown is a comparison chart of the 1C cycle of Comparative Examples 1, 3, and 4 of the present invention;

[0022] Figure 2 The diagram shown is a comparison of the 1C cycle of Embodiment 2 of the present invention with Comparative Examples 1 and 2;

[0023] Figure 3 The diagram shown is a comparison of the 1C cycle of Embodiments 1-3 of the present invention and Comparative Example 1.

[0024] Figure 4 The image shown is a SEM image of the electrode prepared in Comparative Example 1 of this invention.

[0025] Figure 5 The image shown is a SEM image before the cycle in Embodiment 3 of the present invention.

[0026] Figure 6The image shows the Fourier transform infrared spectra of PEDOT:DBSA, GOPS, (PEDOT:DBSA) / GOPS and Example 2 (ZnO@(PEDOT:DBSA) / GOPS) in this invention.

[0027] Figure 7 The image shown is a SEM image of Comparative Example 1 after 100 cycles of the present invention.

[0028] Figure 8 The image shown is a SEM image of Example 3 after 100 cycles of the present invention.

[0029] Figure 9 The figure shows a comparison of the swelling rates of PEDOT:PSS, PEDOT:DBSA, and (PEDOT:DBSA) / GOPS.

[0030] Figure 10 The figure shown is a diagram of the experimental results after one week of immersion in PEDOT:PSS, PEDOT:DBSA, and (PEDOT:DBSA) / GOPS membranes.

[0031] Figure 11 The images shown are photographs of the diaphragms after cycle failure in Comparative Examples 1, 2, and 2 of the present invention. Detailed Implementation

[0032] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the specific implementation methods of the present invention will be described below with reference to the accompanying drawings. Obviously, the drawings described below are merely some embodiments of the present invention. For those skilled in the art, other drawings and other implementation methods can be obtained based on these drawings without any creative effort.

[0033] The present invention proposes a composite zinc-based anode, comprising (1) a substrate electrode and (2) a functionalized material. The functionalized material is coated on the substrate electrode to form a coating layer on the substrate electrode. The coating has high conductivity and establishes a three-dimensional electron transport channel while blocking the electrolyte from corroding the substrate electrode.

[0034] (1) The substrate electrode is a conventional zinc-based negative electrode. For example, the substrate electrode can be a porous zinc-based negative electrode, comprising zinc oxide, metallic zinc, a conductive agent, and a binder, wherein the mass ratio of zinc oxide, metallic zinc, conductive agent, and binder is (60-90):(5-30):(3-15):(2-10). Preferably, the thickness of the substrate electrode is 180-200 μm.

[0035] The substrate electrode is prepared as follows: zinc oxide, metallic zinc, conductive agent and binder are mixed evenly, then coated on the current collector and rolled into shape. The thickness of the substrate electrode is controlled during the rolling process. It is then dried in a vacuum drying oven at 60-100℃, for example 80℃, for 6 hours to form a porous zinc-based negative electrode.

[0036] Preferably, the conductive agent includes one or more of carbon black, graphene, and carbon nanotubes.

[0037] Preferably, the adhesive includes one or more of polytetrafluoroethylene, carboxymethyl cellulose, and styrene-butadiene rubber.

[0038] (2) Functionalized materials, including poly(3,4-ethylenedioxythiophene) (PEDOT), dodecylbenzenesulfonic acid (DBSA), and 3-glycidyl etheroxypropyltrimethoxysilane (GOPS), wherein poly(3,4-ethylenedioxythiophene) and dodecylbenzenesulfonic acid form a PEDOT:DBSA material, and 3-glycidyl etheroxypropyltrimethoxysilane is added to the PEDOT:DBSA material to form a functionalized material. The functionalized material is coated on a substrate electrode to form a coating layer. Preferably, the coating layer thickness is 0.02–20 μm.

[0039] In this invention, the contents of poly(3,4-ethylenedioxythiophene) (PEDOT), dodecylbenzenesulfonic acid (DBSA), and 3-glycidyl etheroxypropyltrimethoxysilane (GOPS) in the functionalized material are determined based on the raw materials used in its preparation process.

[0040] The functionalized material was prepared as follows: Triton X-100 (i.e., polyethylene glycol octylphenyl ether) and 3,4-ethylenedioxythiophene (EDOT) were added to an aqueous solution of sodium dodecylbenzenesulfonate (SDBS), wherein the mass ratio of Triton X-100 to the solvent water in the aqueous solution of sodium dodecylbenzenesulfonate was 1:400. The mixture was stirred until a homogeneous emulsion was formed. Then, a salt solution containing persulfate and ferric salt was added dropwise to the emulsion. After reacting for 48 hours, the emulsion was broken and the mixture was centrifuged and dried to obtain PEDOT:DBSA powder. The PEDOT:DBSA powder was dispersed in an aqueous ethanol solution, and 3-glycidyl etheroxypropyltrimethoxysilane was added to prepare a dispersion of the functionalized material.

[0041] Preferably, PEDOT:DBSA powder is dispersed in ultrapure water (i.e., an ethanol-water solution) containing 20% ​​anhydrous ethanol to prepare a dispersion with a PEDOT:DBSA powder mass fraction of 1%, and GOPS is added, accounting for 0.05 to 2 vol.% of the dispersion. GOPS is in liquid state and is added to the dispersion at a volume percentage of 0.05 to 2 vol.%.

[0042] The concentration of sodium dodecylbenzenesulfonate aqueous solution is 0.125 mol / L, and the molar ratio of SDBS to EDOT is 1:2.

[0043] In the salt solution, the preferred persulfate is Na2S2O8, the molar ratio of persulfate to EDOT is 1:1, the preferred ferric salt is FeCl3·6H2O, and the ferric salt accounts for 1 wt.% of the mass of the persulfate in the salt solution.

[0044] In the preparation of functionalized materials, after adding salt solution to the emulsion, the solvent content in the reaction system is relatively small. After reacting for 48 hours, three times the volume of solvent in the reaction system, i.e., water, is added, and demulsification is performed.

[0045] In this invention, the contents of poly(3,4-ethylenedioxythiophene), dodecylbenzenesulfonic acid and 3-glycidyl etheroxypropyltrimethoxysilane in the functionalized material are determined based on the amount of EDOT used during preparation.

[0046] The method for preparing the composite zinc-based negative electrode of the present invention includes the preparation of the substrate electrode sheet and the preparation of the functionalized material as described above, and further includes coating, as follows:

[0047] A dispersion containing PEDOT:DBSA powder and GOPS crosslinking agent was drop-coated onto a substrate electrode, vacuum dried at 40°C, the solvent of the dispersion was dried off, and then transferred to 60-100°C, for example 80°C, for 2 hours to continue drying and curing, forming a composite zinc-based negative electrode with a coating layer.

[0048] In conventional nickel-zinc batteries, the negative electrode active material is metallic zinc, which is oxidized to zinc hydroxide during discharge and eventually converted to zinc oxide. During charging, zinc oxide is converted back to zinc. Generally, the negative electrode can be either metallic zinc or zinc oxide, with the addition of oxy-zinc oxide to improve electrode stability. However, uneven zinc ion deposition during charge and discharge can easily lead to dendrite formation, and excessive penetration of the separator can cause a short circuit. Furthermore, the spontaneous reaction of zinc in alkaline electrolytes: Zn + H₂O → ZnO + H₂, causes capacity loss and hydrogen evolution. This invention uses PEDOT and DBSA to construct a continuous coating layer of highly conductive polymers. The PEDOT:DBSA system is stable in aqueous solution and does not dissolve in potassium hydroxide electrolyte. The coating layer formed based on PEDOT:DBSA has a good electrolyte barrier effect. Furthermore, the coating layer establishes a three-dimensional electron transport channel, resulting in high conductivity without affecting the negative electrode performance. GOPS crosslinking agent covalently bonds with the sulfonate groups in PEDOT:DBSA to form a stable three-dimensional crosslinked network structure, reducing the penetration of water molecules into the coating layer and improving the stability of the coating layer. In addition, the silanol groups generated by the hydrolysis of GOPS interact with the zinc oxide of the substrate anode, improving the bonding strength between the coating layer and the substrate anode.

[0049] This invention adds only one step to the existing nickel-zinc battery anode production process: a functionalized material dispersion coating process. This eliminates the need for significant modifications to the anode production process and avoids the conventional secondary conductive coating treatment of zinc oxide powder, thus simplifying the production flow. The functionalized material of this invention forms a coating layer on the substrate electrode. Through the dual effects of chemical cross-linking and interfacial bonding, the swelling rate of the coating layer is significantly reduced while the interfacial bonding strength between the coating layer and the substrate electrode is improved.

[0050] The conductive polymer network of the coating layer in this invention forms a multi-level protection mechanism: the three-dimensional conductive framework homogenizes the electric field distribution on the electrode surface through electrostatic shielding, blocking the preferred orientation growth path of dendrites; the coating layer prevents direct contact between the electrolyte and the substrate electrode, inhibiting hydrogen evolution and corrosion reactions, and limiting the growth of Zn(OH)4. 2- The diffusion of Zn(OH)4 was inhibited. 2- The decomposition produces ZnO deposits that passivate the electrodes and block the pores of the diaphragm.

[0051] The technical solution of the present invention will be described in detail below with specific embodiments.

[0052] Unless otherwise specified in the embodiments and comparative examples of this invention, the conditions were performed under conventional conditions or conditions recommended by the manufacturer. All raw materials and reagents used, unless otherwise specified, were commercially available products.

[0053] Example 1

[0054] Zinc oxide, zinc powder, conductive carbon (C45), and PTFE emulsion (containing polytetrafluoroethylene polymer chemical material, with a solid content of 60%) in a mass ratio of 75:10:10:5 are mixed with a 95% volume ethanol solution to form a paste, which is then uniformly rolled onto the surface of a brass mesh current collector to form a P-ZnO substrate electrode.

[0055] A 1 wt.% PEDOT:DBSA dispersion was prepared. The solvent for the dispersant was ultrapure water containing 20% ​​anhydrous ethanol (the same applies below). 0.05 vol.% GOPS was added, and the mixture was ultrasonically dispersed for 10 min to obtain a dispersion of the functionalized material. 20 μL of the dispersion was drop-coated onto a P-ZnO electrode, vacuum dried at 40 °C, and then cured at 80 °C for 2 h to obtain a composite zinc-based anode (ZnO@(PEDOT:DBSA) / 0.05% GOPS).

[0056] Example 2

[0057] Zinc oxide, zinc powder, conductive carbon (C45), and PTFE emulsion (containing polytetrafluoroethylene polymer chemical material, with a solid content of 60%) in a mass ratio of 75:10:10:5 are mixed with a 95% volume ethanol solution to form a paste, which is then uniformly rolled onto the surface of a brass mesh current collector to form a P-ZnO substrate electrode.

[0058] A 1 wt.% PEDOT:DBSA dispersion was prepared and 0.5 vol.% GOPS was added. The mixture was ultrasonically dispersed for 10 min to obtain a dispersion of the functionalized material. 20 μL of the dispersion was drop-coated onto a P-ZnO electrode and dried under vacuum at 40 °C. The electrode was then cured at 80 °C for 2 h to obtain a composite zinc-based anode (ZnO@(PEDOT:DBSA) / GOPS).

[0059] Example 3

[0060] Zinc oxide, zinc powder, conductive carbon (C45), and PTFE emulsion (containing polytetrafluoroethylene polymer chemical material, with a solid content of 60%) in a mass ratio of 75:10:10:5 are mixed with a 95% volume ethanol solution to form a paste, which is then uniformly rolled onto the surface of a brass mesh current collector to form a P-ZnO substrate electrode.

[0061] A 1 wt.% PEDOT:DBSA dispersion was prepared and 2 vol.% GOPS was added. The dispersion was ultrasonically dispersed for 10 min to obtain a dispersion of functionalized material. 20 μL of the dispersion was drop-coated onto a P-ZnO electrode, dried under vacuum at 40 °C, and then cured at 80 °C for 2 h to obtain a composite zinc-based anode (ZnO@(PEDOT:DBSA) / 2% GOPS).

[0062] Comparative Example 1

[0063] No functional materials were added to this comparative example.

[0064] Zinc oxide, zinc powder, conductive carbon (C45), and PTFE emulsion (containing polytetrafluoroethylene polymer chemical material, with a solid content of 60%) in a mass ratio of 75:10:10:5 are mixed with a 95% volume ethanol solution to form a paste, which is then uniformly rolled onto the surface of a brass mesh current collector to form a P-ZnO substrate electrode.

[0065] Comparative Example 2

[0066] Compared with Example 2, this comparative example uses PSS (polystyrene sulfonic acid) instead of DBSA, and PEDOT:PSS is commercially available PEDOT:PSS OE-000, the same below.

[0067] Zinc oxide, zinc powder, conductive carbon (C45), and PTFE emulsion (containing polytetrafluoroethylene polymer chemical material, with a solid content of 60%) in a mass ratio of 75:10:10:5 are mixed with a 95% volume ethanol solution to form a paste, which is then uniformly rolled onto the surface of a brass mesh current collector to form a P-ZnO substrate electrode.

[0068] A 1 wt.% PEDOT:PSS dispersion was prepared and 0.5 vol.% GOPS was added. The mixture was ultrasonically dispersed for 10 min. 20 μL of the dispersion was drop-coated onto a P-ZnO electrode and dried under vacuum at 40 °C. The electrode was then cured at 80 °C for 2 h to obtain a composite zinc-based anode (ZnO@(PEDOT:PSS) / GOPS).

[0069] Comparative Example 3

[0070] Compared to Comparative Example 2, this comparative example did not include GOPS.

[0071] Zinc oxide, zinc powder, conductive carbon (C45), and PTFE emulsion (containing polytetrafluoroethylene polymer chemical material, with a solid content of 60%) in a mass ratio of 75:10:10:5 are mixed with a 95% volume ethanol solution to form a paste, which is then uniformly rolled onto the surface of a brass mesh current collector to form a P-ZnO substrate electrode.

[0072] A 1 wt.% PEDOT:PSS dispersion was prepared, and 20 μL of the dispersion was drop-coated onto a P-ZnO electrode. After vacuum drying at 40 °C, it was cured at 80 °C for 2 h to obtain a composite zinc-based anode (ZnO@(PEDOT:PSS)).

[0073] Comparative Example 4

[0074] Compared with Examples 1-3, no GOPS was added to this comparative example.

[0075] Zinc oxide, zinc powder, conductive carbon (C45), and PTFE emulsion (containing polytetrafluoroethylene polymer chemical material, with a solid content of 60%) in a mass ratio of 75:10:10:5 are mixed with a 95% volume ethanol solution to form a paste, which is then uniformly rolled onto the surface of a brass mesh current collector to form a P-ZnO substrate electrode.

[0076] A 1 wt.% PEDOT:DBSA dispersion was prepared, and 20 μL of the dispersion was drop-coated onto a P-ZnO electrode. After vacuum drying at 40 °C, it was cured at 80 °C for 2 h to obtain a composite zinc-based anode (ZnO@(PEDOT:DBSA)).

[0077] The negative electrodes of Examples 1-3 and Comparative Examples 1-4, along with Ni(OH)2 positive electrodes and cellulose / glass cellulose composite separators, were assembled into nickel-zinc batteries using 7M KOH-saturated ZnO electrolyte. The long-cycle performance at 1C rate was then tested. Figure 1-3 As shown.

[0078] SEM images of the electrodes prepared in Example 2 and Comparative Example 1 before cycling are shown below. Figure 4-5 As shown, the SEM image after 100 cycles is as follows. Figure 7-8 As shown.

[0079] The results showed that although the cycle life of the ZnO@(PEDOT:PSS) electrode (176 cycles) was improved compared to P-ZnO (102 cycles), it was still significantly lower than that of ZnO@(PEDOT:DBSA) (241 cycles). Figure 1 (as shown);

[0080] Combination Figure 9 , 10 This demonstrates that improved film stability does indeed contribute to improved battery cycle stability. The ZnO@(PEDOT:DBSA) / GOPS in Example 2 exhibited the longest cycle life. This is because GOPS, through both chemical crosslinking and interfacial bonding, significantly reduced the swelling ratio of the coating while simultaneously increasing the interfacial bonding strength, thus enhancing the mechanical strength and chemical stability of the coating. Figure 6 , 9 10). The conductive network in the coating and the zinc-philic groups (-SO3) - The -S- group promotes efficient electron and ion transport, while simultaneously inducing Zn(OH)4. 2- Preferential adsorption, reconstruction of the electric double layer, and reduction of Zn(OH)4 2- The desolvation energy reduces side reactions and accelerates interfacial reaction kinetics. Furthermore, this conductive polymer network homogenizes the current density, and the electrostatic shielding effect effectively suppresses dendrite growth. Figure 7 , 8 The coating layer confines Zn(OH)42- The diffusion of Zn(OH)4 was inhibited. 2- The decomposition produces ZnO deposits that passivate the electrodes and block the pores of the diaphragm. Figure 11 This results in ZnO@(PEDOT:DBSA) / GOPS exhibiting excellent overall electrochemical performance. In full-cell testing, it achieved stable cycling at 1C for 370 cycles.

[0081] The embodiments provided by the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention, and the descriptions of the embodiments above are only for the purpose of helping to understand the core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.

Claims

1. A composite zinc-based negative electrode, characterized in that, The device includes a substrate electrode and functionalized materials. The functionalized materials are coated on the substrate electrode to form a coating layer. The functionalized materials include poly(3,4-ethylenedioxythiophene), dodecylbenzenesulfonic acid, and 3-glycidyl etheroxypropyltrimethoxysilane. Poly(3,4-ethylenedioxythiophene) and dodecylbenzenesulfonic acid form a poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid material. 3-glycidyl etheroxypropyltrimethoxysilane is added to the poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid material to form the functionalized material. The preparation steps of the composite zinc-based anode are as follows: Polyethylene glycol octylphenyl ether and 3,4-ethylenedioxythiophene were added to an aqueous solution of sodium dodecylbenzenesulfonate and stirred until a homogeneous emulsion was formed. Then, a salt solution containing persulfate and ferric salt was added dropwise to the emulsion. After reacting for 48 hours, the emulsion was broken and the mixture was centrifuged and dried to obtain poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid powder. The poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid powder was dispersed in an aqueous ethanol solution, and 3-glycidyl etheroxypropyltrimethoxysilane was added to prepare a dispersion of the functionalized material. A dispersion containing poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid powder and 3-glycidyl etheroxypropyltrimethoxysilane crosslinking agent was drop-coated onto a substrate electrode, dried under vacuum at 40°C, the solvent of the dispersion was dried off, and then transferred to 80°C for further drying and curing for 2 hours to form a composite zinc-based negative electrode with a coating layer. The substrate electrode is a porous zinc-based negative electrode. Zinc oxide, metallic zinc, conductive agent and binder are mixed evenly, then coated on the current collector and rolled into shape, and dried in a vacuum drying oven at 60-100℃ to form a porous zinc-based negative electrode.

2. The composite zinc-based negative electrode according to claim 1, characterized in that, The substrate electrode comprises zinc oxide, metallic zinc, conductive agent and binder, wherein the mass ratio of zinc oxide, metallic zinc, conductive agent and binder is (60-90):(5-30):(3-15):(2-10).

3. The composite zinc-based negative electrode according to claim 2, characterized in that, The thickness of the coating layer is 0.02–20 μm.

4. The composite zinc-based negative electrode according to claim 2, characterized in that, The thickness of the substrate electrode is 180–200 μm.

5. A method for preparing a composite zinc-based negative electrode, characterized in that, The composite zinc-based anode as described in any one of claims 2-4 is prepared as follows: Preparation of functionalized materials: Polyethylene glycol octylphenyl ether and 3,4-ethylenedioxythiophene were added to an aqueous solution of sodium dodecylbenzenesulfonate and stirred until a homogeneous emulsion was formed. Then, a salt solution containing persulfate and ferric salt was added dropwise to the emulsion. After reacting for 48 hours, the emulsion was broken and the mixture was centrifuged and dried to obtain poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid powder. The poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid powder was dispersed in an aqueous ethanol solution, and 3-glycidyl etheroxypropyltrimethoxysilane was added to prepare a dispersion of the functionalized material. Coating: A dispersion containing poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid powder and 3-glycidyl etheroxypropyltrimethoxysilane crosslinking agent is drop-coated onto a substrate electrode, vacuum dried at 40°C, the solvent of the dispersion is dried off, and then transferred to 80°C for further drying and curing for 2 hours to form a composite zinc-based negative electrode with a coating layer.

6. The preparation method according to claim 5, characterized in that, Poly(3,4-ethylenedioxythiophene):dodecylbenzenesulfonic acid powder was dispersed in ultrapure water containing 20% ​​anhydrous ethanol to prepare a 1% (w / w) dispersion, and 3-glycidyl etheroxypropyltrimethoxysilane was added, with 3-glycidyl etheroxypropyltrimethoxysilane accounting for 0.05-2 vol.% of the dispersion.

7. The preparation method according to claim 5, characterized in that, The concentration of the sodium dodecylbenzenesulfonate aqueous solution is 0.125 mol / L, and the molar ratio of sodium dodecylbenzenesulfonate to 3,4-ethylenedioxythiophene is 1:

2.

8. The preparation method according to claim 5, characterized in that, In the salt solution, the persulfate includes Na2S2O8, and the molar ratio of persulfate to 3,4-ethylenedioxythiophene is 1:

1. The ferric salt includes FeCl3·6H2O, and the ferric salt accounts for 1 wt.% of the mass of the persulfate in the salt solution.

9. The preparation method according to any one of claims 5-8, characterized in that, The preparation method also includes the preparation of the substrate electrode: Zinc oxide, metallic zinc, conductive agent, and binder are mixed evenly, then coated onto the current collector and rolled into shape. The thickness of the substrate electrode is controlled during the rolling process. The electrode is then dried in a vacuum drying oven at 60–100°C to form a porous zinc-based negative electrode.

10. An application of a composite zinc-based negative electrode, characterized in that, The composite zinc-based negative electrode as described in any one of claims 1-4 is used in an alkaline nickel-zinc battery.

Citation Information

Patent Citations

  • Modified zinc electrode material and preparation method and application thereof

    CN119108546A

  • Negative electrode material for zinc secondary battery, preparation method of negative electrode material, negative electrode plate and battery

    CN119133419A